Analysis of the Impact of Covid-19 on the Implementation of Internal Audit Procedures in Indonesia - La Ode Abdullah; Nova Widodo; Sasmito Nugroho (Politeknik Negeri Madiun, 2022)
Currently the world is under heavy pressure due to the outbreak of the covid-19 virus. The WFH policy for employees also has an impact on internal auditors, internal auditors must adjust to the conditions and schedules of employees. Remote auditing is the best alternative for auditors to complete their work during a pandemic. This study aims to analyse the impact of Covid-19 on internal audit procedures. The researcher in conducting the analysis uses qualitative methods with primary and secondary data sources, while the type of data used is qualitative. Data collection methods are interviews and documentation. The results of the data analysis were then validated for drawing conclusions. The results of the study show that the internal audit/review procedure during the COVID-19 pandemic has undergone several changes in its implementation. data analysis which shows that inspection procedures at private institutions at all stages of implementation are carried out remotely or online, Meanwhile, in Public accounting Firm, all stages of implementation are carried out remotely or online, except for the inspection stage which is carried out in person and remotely. Based on the results of data analysis, it shows that auditors from agencies and auditors from Public Accounting Firm have carried out remote audits, but there are also those who still combine them with traditional audits.